Use of granulated rubber in asphalt mixtures: A literary review - Hoyos Díaz, Luz Magali (2025)
Millions of tons of discarded tires are produced each year, presenting a serious environmental problem. Due to this, granulated rubber (CR) is currently being used in the design of asphalt mixtures, since they provide fundamental properties in it, such as durability and resistance. In this research, different articles were analyzed with the aim of deciphering the processes and methods used with the use of CR, identifying the optimal percentages and the improvement it provides in asphalt mixtures. It was found that the optimum percentages of CR in the asphalt mixtures vary in a range of 1% -20% by weight of the total mixture. Likewise, using CR provides different benefits to the mixture such as: resistance to indirect traction, susceptibility, humidity, grooving, permeability, and aging; increases the useful life of the mixtures to fatigue; and reduces noise. Fifty articles indexed in the Scopus database between 2006 and 2020 were reviewed on the use of CR in asphalt mixtures, moisture damage, resistance to furrow formation, resistance to fatigue and resistance to low temperature.